Revisiting ROS: duality in organ aging progression - Mohan Yu; Shiyi Liu; Chenxin Zhang; Wen Yang (Molecular Biology Reports, 2026)

Elevated contaminations and risks of novel organophosphate esters and their transformation products in paddy soils - Zixiao Zhao; Meng Gao; Mohan Ma; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; Hongwen Sun (Journal of Environmental Sciences, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Reinforcing electrolyte skeleton via in-situ cross-link enhancement for solid-state lithium metal batteries - Ziwen Tian; Mohan Yang; Yutao Wang; Qiwei Wu; Yu Guan; Hao Men; Yali Li; Lian Wang; Yuefeng Su; Yong Zhao (Chemical Engineering Journal, 2026)

Synergistic gel-carrier immobilization strategy for anaerobic ammonia-oxidizing bacteria: Micro-spatial distribution and microbial community synergy - Wenshan He; Guo-hua Liu; Zhen Huang; Mohan Gao; Yang Qin; Suying Ding; Xiao-jun Wang; Yu-qian Shi; Lu Qi; Hongchen Wang (Journal of Environmental Chemical Engineering, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Phytochemistry and nutraceutical potential of Ceylon Cinnamomum species native to Sri Lanka - Lakmal Gonawala; Maheehsa Madhumaali; Hanouf Ismail; Nishara Jayasooriya; Nalaka Wijekoon; Shanuk Rajapakshe; Harshanie Erangika; Dhammika Amaratunga; Rajitha Gunaratna; Harry W.M. Steinbusch; Chandra Mohan; Yu-Chung Chiang; et al. (Natural Product Research, 2026)

Basic amino acid-enriched egg white peptides for efficient repair of intestinal injury: Preparation, application, and mechanism analysis - Qingwen Han; Jingbo Liu; Shengrao Li; Mohan Zhang; Weiyi Ma; Yanguo Huan; Dongfang Wang; Yongqi Yu; Ting Zhang; Siwen Lyu (Food Research International, 2026)

Regulation of lipid metabolism and flavor formation in Tianfu broiler chickens via the circ_015424/miR-196-1-3p/MOGAT1 axis - Zhi Hu; Jiapeng Chen; Hengyong Xu; Xuyang Ji; Jiajun Zhu; Longge Guo; Xinqi Wang; Yiping Liu; Chaowu Yang; Chunlin Yu; Zengrong Zhang; Mohan Qiu; et al. (Food Chemistry, 2026)

Modeling Studies of Sources and Pathways of Freshwater Accumulation in the Beaufort Gyre Region - Yu Zhang; Changsheng Chen; Mohan Wang; Deshuai Wang (Journal of Marine Science and Engineering, 2026)
Freshwater accumulation is one of the most striking observations in the Beaufort Gyre (BG) region in the Arctic Ocean. A 39-year simulation, using the validated high-resolution, geometrical-fitting, unstructured grid Finite-Volume Community Ocean Model for the Arctic Ocean, aimed to investigate the contributions of coastal currents and their interannual variability to this phenomenon. The model reasonably reproduced the interannual variability of freshwater content (FWC) in the BG region. Analysis revealed the constructive role of Ekman pumping in supplying FWC, while the lateral flux generally acts to remove FWC from the region. The disparity between Ekman pumping and lateral flux drives the interannual variability of total FWC, with accumulation occurring when the downward Ekman FWC flux surpasses the net outflow-induced lateral FWC flux. Since 2007, there has been a significant increase in downward Ekman pumping, accompanied by a rise in net outflow lateral flux, indicating heightened variability of FWC in the BG region. The model results suggested that the coastal flow over the Arctic continental shelf underwent dramatic changes, especially during summer, and these changes were partially due to increased freshwater and sea ice melting. Increased lateral FWC flux during summer has become a competitive source for unprecedented seasonal freshwater accumulation in the BG region. Flow intensification over the North American coast is influenced by increased freshwater runoff, including the Firth, Kobuk, and Mackenzie Rivers. Interannual FWC variation in the Beaufort Sea could be influenced by the changes in slope flow, with the water originating in part from the Barents and Kara Seas.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Antimicrobial, antioxidant and anticancer properties of bioactive bacteriocins produced by Lactococcus hircilactis CH4 and Lactobacillus delbrueckii GRIPUMSK isolated from homemade fermented dairy products - Moovendran Srinivash; Raman Krishnamoorthi; Pambayan Ulagan Mahalingam; Balasubramanian Malaikozhundan; Muthuramalingam Kaviyadharshini; Mohan Keerthivasan; Pitchaimuthu Rajkannan; Kasi Karuppa Samy; Krishnamoorthy Gurushankar; Yu-Kuo Chung; Jia-You Fang; Sonaimuthu Mohandoss; et al. (International Dairy Journal, 2025)

Synthetic phenolic antioxidants in paddy soils from central China: Contamination characteristics and risk prioritization analysis - Mohan Ma; Meng Gao; Zixiao Zhao; Siyuan Li; Yimeng Si; Liman Wei; Yiting Ge; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; et al. (Environmental Pollution, 2025)

Late Pliocene millennial-scale climate variability response of the South Asian summer monsoon to low-latitude insolation and Antarctic ice sheet forcing - Ze Zhang; Zhixiang Wang; David B. Kemp; Yu Sui; Yanzhen Li; Jiangnan Zhao; Ruiyao Zhang; Anguo Xiao; Mengmeng Cao; Mohan Zhao; Xinya Bai; Chunju Huang (Global and Planetary Change, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of cracked semi-infinite ice sheets on the wave excited motion of a body floating on water - MoHan Zhang; RunShan Xiao; Zhen Xue; FaJun Yu (Ocean Engineering, 2025)

Occurrence & characterization of Staphylococcus aureus from ready-to-eat (RTE), and cooked food in Singapore: A retrospective analysis - Ye Htut Zwe; Roshini Devi Mohan; Si Jia Lim; Wai Ching Lai; Kae Hwan Sim; Yu Lee Leyau; Ker Lew; Joachim Mun Choy Chua; Kyaw Thu Aung; Kern Rei Chng; Yuan Sheng Wu; Joanne Sheot Harn Chan; et al. (International Journal of Food Microbiology, 2025)

Influence of environmental factors on microbial community and flavor profile of dajiang of Liaoning - Shanshan Zhao; Zhichi Zhang; Yu Qiao; Mohan Li; Jiali Chen; Yan Zheng; Xiqing Yue (Food Bioscience, 2025)

Box-shaped necklace-like Fe3O4/MoS2-CNFs composite nanofibers with confinement effect enhancing sodium storage performance - Huayu Wu; Mohan Yue; Lin He; Miao Zhang; Yimin Huang; Chang Sun; Yu Liu; Jindi Wang; Rongguan Lv; Rong Xing (Chemical Engineering Journal, 2025)

miR-24-3p inhibits lipid synthesis and progesterone secretion in chicken granulosa cells via ERK1/2 signaling pathway - Yanrong Gong; Zhongzhen Lin; Hao Sun; Chunlin Yu; Mohan Qiu; Xia Xiong; Lingqian Yin; Donghao Zhang; Yan Wang; Chaowu Yang; Yiping Liu (Theriogenology, 2024)

Tetracycline removal by immobilized indigenous bacterial consortium using biochar and biomass: Removal performance and mechanisms - Xinping Yu; Mohan Bai; Xiaojing Li; Pinpin Yang; Qiuzhen Wang; Zhennan Wang; Liping Weng; Huike Ye (Bioresource Technology, 2024)

Macroscale properties and atomic-scale mechanisms of ash removal in low-temperature hydrothermal carbonization - Yan Yu; Zhangmin Wan; Micholas Dean Smith; Mood Mohan; Shahabaddine Sokhansanj; Anthony Lau; Jeremy C. Smith; Orlando J. Rojas (Chemical Engineering Journal, 2024)

Transcriptome Sequencing and Mass Spectrometry Reveal Genes Involved in the Non-mendelian Inheritance-Mediated Feather Growth Rate in Chicken - Mohan Qiu; Zengrong Zhang; Shiliang Zhu; Siyang Liu; Han Peng; Xia Xiong; Jialei Chen; Chenming Hu; Li Yang; Xiaoyan Song; Bo Xia; Chunlin Yu; et al. (Biochemical Genetics, 2024)
The feather growth rate in chickens included early and late feathering. We attempted to characterize the genes and pathways associated with the feather growth rate in chickens that are not in agreement with Mendelian inheritance. Gene expression profiles in the hair follicle tissues of late-feathering cocks (LC), early-feathering cocks (EC), late-feathering hens (LH), and early-feathering hens (EH) were acquired using RNA sequencing (RNA-seq), mass spectrometry (MS), and quantitative reverse transcription PCR (qRT‑PCR). A total of 188 differentially expressed genes (DEGs) were ascertained in EC vs. LC and 538 DEGs were identified in EH vs. LH. We observed that 14 up-regulated genes and 9 down-regulated genes were screened both in EC vs. LC and EH vs. LH. MS revealed that 41 and 138 differentially expressed proteins (DEPs) were screened out in EC vs. LC and EH vs. LH, respectively. Moreover, these DEGs and DEPs were enriched in multiple feather-related pathways, including JAK-STAT, MAPK, WNT, TGF-β, and calcium signaling pathways. qRT-PCR assay showed that the expression of WNT8A was decreased in LC compared with EC, while ALK and GRM4 expression were significantly up-regulated in EH relative to LH. This study helps to elucidate the potential mechanism of the feather growth rate in chickens that do not conform to genetic law.

Proteomic and phosphoproteomic reveal immune-related function of milk fat globule membrane in bovine milk of different lactation periods - Xue Bai; Jingwen Shang; Xueyan Cao; Mohan Li; Hong Yu; Chunshuang Wu; Mei Yang; Xiqing Yue (Food Chemistry, 2024)

Non-sealed water hastens the efficiency of microbial electrochemical remediation system - Iranzi Emile Rushimisha; Huike Ye; Side Yang; Xin Yu; Mohan Bai; Yali Chen; Benjamin Manirakiza; Xiaojing Li; Yongtao Li (Journal of Cleaner Production, 2024)

Fulvic acid more facilitated the soil electron transfer than humic acid - Side Yang; Kai Wang; Xin Yu; Yan Xu; Huike Ye; Mohan Bai; Lixia Zhao; Yang Sun; Xiaojing Li; Yongtao Li (Journal of Hazardous Materials, 2024)

Environmental surveillance in Jinan city of East China (2014–2022) reveals improved air quality but remained health risks attributable to PM2.5-bound metal contaminants - Zhigang Yu; Zhan Sun; Lanzheng Liu; Chao Li; Xin Zhang; Gzalnur Amat; Mohan Ran; Xiaoyue Hu; Yunxiang Xu; Xiulan Zhao; Jun Zhou (Environmental Pollution, 2024)

Effect of microplastics on the degradation of tetracycline in a soil microbial electric field - Kai Wang; Side Yang; Xin Yu; Yonghong Liu; Mohan Bai; Yan Xu; Liping Weng; Yongtao Li; Xiaojing Li (Journal of Hazardous Materials, 2023)

RNA sequencing reveals lncRNA-mediated non-mendelian inheritance of feather growth change in chickens - Mohan Qiu; Chunlin Yu; Shiliang Zhu; Siyang Liu; Han Peng; Xia Xiong; Jialei Chen; Xiaosong Jiang; Huarui Du; Qingyun Li; Zengrong Zhang; Chaowu Yang (Genes & Genomics, 2022)
Background Long non-coding RNAs (lncRNAs) play an essential role in biological processes. However, the expression patterns of lncRNAs that regulate the non-Mendelian inheritance feather phenotypes remain unknown. Objective This study aimed to compare the expression profiles of lncRNAs in the follicles of the late-feathering cocks (LC) and late-feathering hens (LH) that followed genetic rules and the early-feathering hen (EH) and early-feathering cock (EC) that did not conform to the genetic laws. Methods We performed RNA sequencing and investigated the differentially expressed lncRNAs (DElncRNAs) between the early- and late-feathering chickens, which function by cis-acting or participate in the competing endogenous RNA (ceRNA) network. Results A total of 53 upregulated and 43 downregulated lncRNAs were identified in EC vs. LC, and 58 upregulated and 109 downregulated lncRNAs were identified in EH vs. LH. The target mRNAs regulated by lncRNAs in cis were enriched in the pentose phosphate pathway, TGF-β signaling pathway and Jak-STAT signaling pathway in EC vs. LC and were associated with the TGF-β signaling pathway, Wnt signaling pathway, p53 signaling pathway and Jak-STAT signaling pathway in EH vs. LH. In addition, the lncRNA-mediated ceRNA regulatory pathways of hair follicle formation were mainly enriched in the TGF-β signaling pathway, Wnt signaling pathway, melanogenesis, and calcium signaling pathways. The levels of ENSGALG00000047626 were significantly higher in the late-feathering chickens than in the early-feathering chickens, which regulated the expression of SSTR2 by gga-miR-1649-5p. Conclusion This study provides a novel molecular mechanism of lncRNA’s response to the feather rate that does not conform to the genetic laws in chickens.

High-throughput sequencing revealed the expression profile and potential key molecules of the circular RNAs involved in the process of hypoxic adaptation in Tibetan chickens - Zengrong Zhang; Mohan Qiu; Huarui Du; Qingyun Li; Wu Gan; Xia Xiong; Chunlin Yu; Han Peng; Bo Xia; Xiaoyan Song; Li Yang; Chenming Hu; et al. (Biologia, 2021)

Long Non-coding RNA Expression Profile in Broiler Liver with Cadmium-Induced Oxidative Damage - Chunlin Yu; Chaowu Yang; Xiaoyan Song; Jingjing Li; Han Peng; Mohan Qiu; Li Yang; Huarui Du; Xiaosong Jiang; Yiping Liu (Biological Trace Element Research, 2021)

Effects of free-range broiler production on vegetation characteristic and soil physicochemical property of the stocking areas in China - Chunlin Yu; Xiaosong Jiang; Huarui Du; Qingyun Li; Zengrong Zhang; Mohan Qiu; Tianbao Chen; Bo Xia; Xiaoyan Song; Chenming Hu; Xia Xiong; Li Yang; et al. (Agroforestry Systems, 2020)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Advancing Product Quality: a Summary of the Inaugural FDA/PQRI Conference - Lawrence X. Yu; Jeffrey Baker; Susan C. Berlam; Ashley Boam; E. J. Brandreth; Lucinda Buhse; Thomas Cosgrove; David Doleski; Lynne Ensor; Joseph Famulare; Mohan Ganapathy; Gustavo Grampp; et al. (The AAPS Journal, 2015)

Mapping of the chromosome 17 BMD QTL in the F2 male mice of MRL/MpJ × SJL/J - Hongrun Yu; Bouchra Edderkaoui; Alejandro Cortez; Heather M. Davidson; Jon E. Wergedal; David J. Baylink; Subburaman Mohan (Genetica, 2009)

New quantitative trait loci that regulate wound healing in an intercross progeny from DBA/1J and 129×1/SvJ inbred strains of mice - Godfred L. Masinde; Runzhi Li; Bay Nguyen; Hongrun Yu; Apurva K. Srivastava; Bouchra Edderkaoui; Jon E. Wergedal; David J. Baylink; Subburaman Mohan (Functional & Integrative Genomics, 2006)

Mapping the dominant wound healing and soft tissue regeneration QTL in MRL × CAST - Hongrun Yu; Subburaman Mohan; Godfred L. Masinde; David J. Baylink (Mammalian Genome, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Multiplex inheritance of component phenotypes in a murine model of lupus - Laurence Morel *, , Chandra Mohan; Ying Yu; Joel Schiffenbauer , , Ulri; Nana Tian; Jeff A. Longmate (Mammalian Genome, 1999)